2017
DOI: 10.1016/j.kint.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor regulates fibrosis-associated renal lymphangiogenesis

Abstract: Lymphangiogenesis is correlated with the degree of renal interstitial fibrosis. Pro-fibrotic transforming growth factor β induces VEGF-C production, the main driver of lymphangiogenesis. Connective tissue growth factor (CTGF) is an important determinant of fibrotic tissue remodeling, but its possible involvement in lymphangiogenesis has not been explored. We found prominent lymphangiogenesis during tubulointerstitial fibrosis to be associated with increased expression of CTGF and VEGF-C in human obstructed nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 47 publications
2
67
1
Order By: Relevance
“…Both CCN2 and other matricellular proteins can bind to other receptors, including tropomyosin receptor kinase A (TrkA), integrins, and heparan sulphate proteoglycans. Additionally, CCN2 can interact with growth factors such as TGF-β and vascular endothelial growth factor, and modify their function [33][34][35][36]. In the present study, we have found that CCN2 regulates fibrosis in the kidney and EMT in cultured renal cells via EGFR.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Both CCN2 and other matricellular proteins can bind to other receptors, including tropomyosin receptor kinase A (TrkA), integrins, and heparan sulphate proteoglycans. Additionally, CCN2 can interact with growth factors such as TGF-β and vascular endothelial growth factor, and modify their function [33][34][35][36]. In the present study, we have found that CCN2 regulates fibrosis in the kidney and EMT in cultured renal cells via EGFR.…”
Section: Introductionsupporting
confidence: 56%
“…EGFR and TrkA crosstalk has been previously described in CCN2-stimulated tubular epithelial cells [31] and monocytes [36]. Several studies have shown that K252a, an alkaloid-like kinase inhibitor known to selectively inhibit TrkA kinase activity [43], blocks CCN2(IV)-induced activation of several signalling systems, including mitogen-activated protein kinases (MAPKs), and ECM production [33,43].…”
Section: Ccn2(iv) Regulates Ecm Protein Synthesis In Cultured Renal Fmentioning
confidence: 99%
“…The injury tubules produce a large amount of VEGF-C and VEGF-D during acute kidney injury and chronic kidney disease [49]. Kinashi et al [50] found that connective tissue growth factor (CTGF) is another important determinant of lymphangiogenesis. The increase of LVs and VEGF-C in obstructed and ischemia-reperfusion injury kidneys was significantly reduced in CTGF knockout compared to wild-type mice.…”
Section: Lymphangiogenesis and Kidney Diseasementioning
confidence: 99%
“…VEGF‐A‐knockout mice show losses of podocyte foot processes and endothelial cell fenestrations, suggesting a crucial role for VEGF in maintaining the function of the glomerular filtration barrier (Sison et al, ). In contrast, VEGF expression correlates with fibrotic markers in diabetic kidneys (Kinashi et al, ), and a selective VEGFR‐3 inhibitor ameliorates diabetic kidney injury in db/db mice (Hwang et al, ). Thus, the protective effect of VEGF in the kidney is controversial.…”
Section: Pgc‐1α: a Key Player In Metabolismmentioning
confidence: 99%